1999
DOI: 10.1126/science.285.5425.251
|View full text |Cite
|
Sign up to set email alerts
|

Ploidy Regulation of Gene Expression

Abstract: Microarray-based gene expression analysis identified genes showing ploidy-dependent expression in isogenic Saccharomyces cerevisiae strains that varied in ploidy from haploid to tetraploid. These genes were induced or repressed in proportion to the number of chromosome sets, regardless of the mating type. Ploidy-dependent repression of some G1 cyclins can explain the greater cell size associated with higher ploidies, and suggests ploidy-dependent modifications of cell cycle progression. Moreover, ploidy regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
471
4
14

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 608 publications
(518 citation statements)
references
References 21 publications
29
471
4
14
Order By: Relevance
“…(86) Few genes were upregulated or downregulated in the Arabidopsis autotetraploids, consistent with the findings in yeast, in which a dozen genes were expressed differently in response to ploidy changes in a series of haploid, diploid, triploid and autotetraploid. (88) The data suggest that during autopolyploid formation the dosage-dependent regulatory mechanisms prevail. (89) In another study, Hegarty et al (2005) found dramatic differences in floral gene expression between the allohexaploid hybrid, Senecio cambrensis, its parental taxa Senecio squalidus (diploid) and Senecio vulgaris (tetraploid), and the intermediate triploid (sterile) hybrid Senecio  baxteri.…”
Section: Activation Of Transposons and Changes In Dna Methylation In mentioning
confidence: 98%
“…(86) Few genes were upregulated or downregulated in the Arabidopsis autotetraploids, consistent with the findings in yeast, in which a dozen genes were expressed differently in response to ploidy changes in a series of haploid, diploid, triploid and autotetraploid. (88) The data suggest that during autopolyploid formation the dosage-dependent regulatory mechanisms prevail. (89) In another study, Hegarty et al (2005) found dramatic differences in floral gene expression between the allohexaploid hybrid, Senecio cambrensis, its parental taxa Senecio squalidus (diploid) and Senecio vulgaris (tetraploid), and the intermediate triploid (sterile) hybrid Senecio  baxteri.…”
Section: Activation Of Transposons and Changes In Dna Methylation In mentioning
confidence: 98%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript which might allow them to reach a higher metabolic rate to support nitrogen fixation 65,68 . The intensive DNA synthesis that is required for endoreduplication within bacteroids requires a large quantity of dNTPs that must be supplied by ribonucleotide reductase (RNR) 89 .…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Plant cell endoreduplication is required for the formation of functional nodules, and is dependent on the degradation of mitotic cyclins by anaphase-promoting complex (APC), an E3 ubiquitin ligase 66,67 . The advantages of cellular polyploidy are a higher transcription rate and a higher metabolic rate than cells with the normal 2n DNA content 68 -characteristics that might be important for the invaded plant cells to support bacterial nitrogen fixation (discussed later).…”
Section: Box 2 Mesorhizobium Loti and Lotus Japonicus: Model System Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In a genome-wide transcription analysis, Galitski et al could show that yeast (S. cerevisiae) cells with different ploidy exhibit different patterns of gene expression, providing evidence for a ploidy-driven mechanism of gene regulation. 2 An increase in ploidy strongly correlates with increased cell size, as observed in bacteria, yeast, plants, and animals. [1][2][3] The expression of specific G 1 cyclins is repressed with increasing ploidy, which eventually results in a retarded passage through START (the entry point into the cell cycle) and therefore a larger cell size.…”
Section: Introductionmentioning
confidence: 99%